New Born Calf Serum Can Induce Spheroid Formation in Breast Cancer KAIMRC1 Cell Line - Ali, Rizwan; Huwaizi, Sarah; Alhallaj, Alshaimaa; Al Subait, Arwa; Barhoumi, Tlili; Al Zahrani, Hajar; Al Anazi, Abdullah; Latif Khan, Abdul; Boudjelal, Mohamed (Frontiers in Molecular Biosciences, 2021)
3-dimensional (3D) cell culture systems have become very popular in the field of drug screening and discovery. There is an immense demand for highly efficient and easy methods to produce 3D spheroids in any cell format. We have developed a novel and easy method to produce spheroids from the newly isolated KAIMRC1 cell line in vitro. It can be used as a 3D model to study proliferation, differentiation, cell death, and drug response of cancer cells. Our procedure requires growth media supplemented with 10% New Born Calf Serum (NBCS) and regular cell culture plates to generate KAIMRC1 spheroids without the need for any specialized 3D cell culture system. This procedure generates multiple spheroids within a 12-24 h culture. KAIMRC1 spheroids are compact, homogeneous in size and morphology with a mean size of 55.8 µm (±3.5). High content imaging (HCI) of KAIMRC1 spheroids treated with a panel of 240 compounds resulted in the identification of several highly specific compounds towards spheroids. Immunophenotyping of KAIMRC1 spheroids revealed phosphorylation of FAK, cJUN and E-cadherin which suggests the involvement of JNK/JUN pathway in the KAIMRC1 spheroids formation. Gene expression analysis showed upregulation of cell junction genes, GJB3, DSC1, CLDN5 CLDN8 and PLAU. Furthermore, co-culture of KAIMRC1 cells with primary Cancer associated-fibroblasts (CAFs) showcased the potential of these cells in drug discovery application.